Statistical Approach to Regulation of Nanotechnology: Need, Advantages and Disadvantages - Santana Cabello, Ricardo (2020)
The need to have an express regulation covering nanotechnology has been the subject of debate in the scientific literature and identified as one of the main subsets of nanotechnology field research. However, most countries still do not have regulatory framework in order to guarantee consumer safety. This is the case of Costa Rica, one of the most promising countries in Latin America in terms of biotechnology and nanotechnology. This article presents a statistical study about the position of industry, academia and government institutions on the need to expressly regulate nanotechnology in Costa Rica. A qualitative study consisting of a survey of 79 forms was done to individuals representing the community involved with nanotechnology and institutions responsible for ensuring the safety of the citizen’s health, to conclude that the nanotechnology regulation should be created to protect the consumer in Costa Rica. The research also proposes aspects that should be taken into account in its drafting as well as the variables on which decisions should be made to authorize the commercialization of nanomaterials based on the findings of the literature.